Science, nomenclature et représentation. L’expérience et l’expérimentation dans La Joie de vivre d’Émile Zola - Rachwalska von Rejchwald, Jolanta (Studia Romanica Posnaniensia, 2020)
The article presents a strict interpenetration of scientific discourse and literary fiction on the example of Zolaʼs La Joie de vivre. The coexistence of these discourses is part of the poetics of ambiguity, which is characteristic of the weave of literature and science, where Science opposes Doubt. The purpose of the article is to reflect on the relationship between Experience (everyday life) and Experience (scientific). This conceptual opposition is embodied in a pair of main characters: Pauline and Lazare, equipped with a different attitude to reality and science. She learns human physiology by experiencing changes in her maturing body, which appears to her as a complex, but full of secrets, beautiful machinery. He lives by fearing the body and seeing it as the source of death. He wants to defeat death by coming up with experimental designs that are supposed to make him great and bring immortality. His failures lead him to Doubt and negation of science. Zola decides nothing balancing between knowledge and doubt, affirmation of life and the inevitability of death.